Late onset apical hypertrophic cardiomyopathy: a case report. Issue 1 (12th December 2020) - Doeblin, Patrick; Gebker, Rolf; Pieske, Burkert; Kelle, Sebastian
Abstract: Background: Apical hypertrophic cardiomyopathy provides diagnostic challenges through varying presentation, impaired visualization on echocardiography and dissent on diagnostic criteria. While hypertrophic cardiomyopathy in general requires an absolute wall thickness ≥15 mm, a threshold for relative apical hypertrophy (ratio 1.5) has been proposed. Case summary: We report the case of a 57-year-old man with newly arisen chest pain and slight T-wave inversions. Serial cardiac magnetic resonance imaging over 9 years documented the gradual evolvement of late-onset apical hypertrophy with apical fibrosis and strain abnormalities. Symptoms, electrocardiographic changes, and relative apical hypertrophy preceded the traditional imaging criteria of hypertrophic cardiomyopathy. Discussion: Relative apical hypertrophy can be an early manifestation of apical hypertrophic cardiomyopathy. Persistent cardiac signs and symptoms warrant a follow-up, as apical hypertrophic cardiomyopathy can evolve over time. Cardiac magnetic resonance imaging readily visualizes apical hypertrophic cardiomyopathy and associated changes in tissue composition and function.